Human trk oncogenes activated by point mutation, in-frame deletion, and duplication of the tyrosine kinase domain. - Coulier, F (1990)
Malignant activation of the human trk proto-oncogene, a member of the tyrosine protein kinase receptor family, has been implicated in the development of certain human cancers, including colon and thyroid papillary carcinomas. trk oncogenes have also been identified in cultured cells transfected with various DNAs. In this study, we report the characterization of three in vitro-generated trk oncogenes, trk2, trk4, and trk5 (R. Oskam, F. Coulier, M. Ernst, D. Martin-Zanca, and M. Barbacid, Proc. Natl. Acad. Sci. USA 85:2964-2968, 1988), in an effort to understand the spectrum of mutational events that can activate the human trk gene. Nucleotide sequence analysis of cDNA clones of trk2 and trk4 revealed that these oncogenes were generated by a head-to-tail arrangement of two trk tyrosine protein kinase domains connected by a purine-rich region. These oncogenes code for cytoplasmic molecules of 67,000 (p67trk2) and 69,000 (p69trk4) daltons. In contrast, the product of the trk5 oncogene, gp95trk5, is a cell surface glycoprotein of 95,000 daltons. This oncogene was generated by a 153-base-pair in-frame deletion within sequences coding for the extracellular domain of the trk receptor. This activating deletion encompasses a triplet coding for one of the nine cysteine residues that the trk receptor shares with the product of the highly related trkB tyrosine protein kinase gene. Introduction of a single point mutation (TGT----AGT) in this codon resulted in a novel trk oncogene whose product, gp140S345, differs from the nontransforming trk proto-oncogene receptor in a single amino acid residue, Ser-345 instead of Cys-345. These results illustrate that multiple molecular mechanisms, including point mutation, internal deletion, and kinase domain duplication, can result in the malignant activation of the human trk proto-oncogene.